PEMANFAATAN KEGIATAN TAHFIDZ AL-QUR`AN DALAM PEMBENTUKAN KARAKTER ANAK DI DESA SEKODI KECAMATAN BENGKALIS - Aisyah, Aisyah; Sulsitia, Erna; Robiaah, Robiaah (STAI Darul Qalam Tangerang, 2023)
Tahfidz Al-Qur'an is a process of guarding and maintaining the purity of the holy book Al-Qur'an which was revealed by ALLAH SWT, it is so important for us to read the Al-Qur'an because the wisdom and virtue for those who are able to read the Al-Qur'an are very important. Extraordinary. Then this study aims to find out how the holding of Al-Qur'an tahfidz activities can shape children's character. This research was conducted in Sekodi village, Bengkalis sub-district, using qualitative descriptive research with data collection methods used, namely interviews, observation and documentation. From the results of the study it was found that by holding tahfidz Al-Qur'an activities in the formation of this child's character, especially the formation of the disciplinary character of children who took part in tahfidz Al-Qur'an activities had started well and developed, in which children had shows that they have a self-disciplined character, but there are still two or three children who need to be given more guidance. The instilling of discipline character values ​​in these children was also carried out well by the teachers who fostered Al-Qur'an tahfidz activities. Children's character must be instilled in them from an early age. Various methods are carried out in order to instill the character of discipline, namely by motivating students to memorize, read and study the Al-Qur'an which is very important and the various benefits and lessons that we will get, applying rules, teaching discipline on time and so on